Utility and Applicability of Rapid Diagnostic Testing in Antimicrobial Stewardship in the Asia-Pacific Region: A Delphi Consensus - Apisarnthanarak, Anucha; Bin Kim, Hong; Moore, Luke S P; Xiao, Yonghong; Singh, Sanjeev; Doi, Yohei; Kwa, Andrea Lay-Hoon; Ponnampalavanar, Sasheela Sri La Sri; Cao, Qing; Kim, Shin-Woo; Lee, Hyukmin; Santanirand, Pitak (Clinical infectious diseases, 2022)
Abstract Rapid diagnostic tests (RDTs) facilitate fast and accurate identification of infectious disease microorganisms and are a valuable component of multimodal antimicrobial stewardship (AMS) programs but are currently underutilized in the Asia-Pacific region. An experienced group of infectious diseases clinicians, clinical microbiologists, and a clinical pharmacist used a modified Delphi consensus approach to construct 10 statements, aiming to optimize the utility and applicability of infection-related RDTs for AMS in the Asia-Pacific region. They provide guidance on definition, types, optimal deployment, measuring effectiveness, and overcoming key challenges. The Grading of Recommendations Assessment, Development, and Evaluation system was applied to indicate the strength of the recommendation and the quality of the underlying evidence. Given the diversity of the Asia-Pacific region, the trajectory of RDT development will vary widely; the collection of local data should be prioritized to allow realization and optimization of the full benefits of RDTs in AMS. A group of experienced practitioners provide 10 consensus statements for guiding the use of rapid diagnostic tests in antimicrobial stewardship in the Asia-Pacific region, including definitions, types, optimal deployment, measuring effectiveness, and overcoming key challenges.